(untitled) (Al-Academy, 2016)
At the beginning of the twentieth century distorting handling totalitarian phenomena of art, which can be called the stage of the test, transition from the theory of ideal theory and other realistic is not cushy, since it requires vision and reading and other concepts, and in light of this dialectic manifested research problem by asking the following Is affected by the design idealism and realism. Through the above mentioned questions, the researcher found rationale for addressing this problem, the study through his research, which is marked (idealism and realism in a comparative study design). And demonstrated the importance of research in the identification of the concept and the effectiveness of the two theories idealism and realism and its impact in the design, while the aim of the research is the detection of the vulnerability of the art design Balnzeratin idealism and realism, while the boundaries of research have included the reduction objective which specifies study the concept and effectiveness of theories idealism and realism, and their impact on design comparative study, and reducing the spatial determine studying Covers scientific journals, has been the adoption of the length of time of the year 2010 until the year 2011, either the second chapter has included four sections dealing with the first section the concept of the theory either second topic addressed the criticism of the theory and its conformity with the design and effectiveness of the design through theory, then this was followed by indicators of the two theories and design side. Then the third section, which included measures of research and adopted a comparative approach, which Eetmisbethdid similarities and differences between the two incidents either method of selecting the sample Vtm random sampling, either tool, sample analysis, it is through the design of vertebrae form derived paragraphs of indicators theoretical framework, and came fourth section, which included the most important results are as follows: 1. used mechanisms and processes of design to highlight the structural idea, such as hiring exciting visual and who appeared color gives the impression of heat and warmth, a Red doing his job in the expression and show the case of antagonism leading the movement for the effect of the color red in drawing attention. 2 use the formal condensation of the open space, which suggests some sort of closure stationed in the center of the design and the employment of image diagnosis preamplifier In an ideal situation (fictional) show aesthetic qualities